α = ∫ − ∞ ∞ ( 2 cosh x + ϕ ) ( 2 cosh x + ϕ 1 ) d x ∫ − ∞ ∞ ( 2 cosh x − ϕ ) ( 2 cosh x − ϕ 1 ) d x
For α as defined above, where ϕ = 2 5 + 1 , find α 2 − 7 α .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Note that F ( a ) = ∫ − ∞ ∞ 2 cosh x − a 1 d x = ∫ − ∞ ∞ e 2 x − a e x + 1 e x d x = [ 4 − a 2 2 tan − 1 ( 4 − a 2 2 e x − a ) ] − ∞ ∞ = 4 − a 2 1 { π + 2 tan − 1 ( 4 − a 2 a ) } for any ∣ a ∣ < 2 , and hence ∫ − ∞ ∞ ( 2 cosh x − a ) ( 2 cosh x − a − 1 ) 1 d x = a − a − 1 1 ( F ( a ) − F ( a − 1 ) ) for any 2 1 < ∣ a ∣ < 2 . The ratio we are interested in is α = F ( − ϕ − 1 ) − F ( − ϕ ) F ( ϕ ) − F ( ϕ − 1 ) (recall that ϕ − ϕ − 1 = 1 ). After much simplification, we obtain α = 2 1 ( 7 + 5 5 ) and hence α 2 − 7 α = 1 9 .